THE ROLE OF THE ERASMUS+ PROGRAM IN SCHOOL MANAGEMENT - BOLOJAN GEORGETA; BOGHEANU CORINA DANIELA; NEN MADLENA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
The main purpose of this research article is to highlight the benefits brought by the Erasmus+ program in the professional and personal development of teachers participating in mobilities, thus adding value to the institutional management process. The main goal of the study is to first obtain a general picture of the degree of satisfaction of students enrolled in courses offered through the Erasmus + program in the field of education between 2020 and 2023, with a focus on the development of professional and personal skills, including emotional intelligence. Next, the study aims to identify success factors for the management of educational institutions where participatory leadership has been highlighted through the team responsible for promoting and carrying out the Erasmus + program as the project coordinator or consortium coordinator for that specific period. To emphasize the main benefits that the Erasmus+ program provides for both academic management and more specifically organizational leadership, our qualitative research narrows down from general to specific and is based on the following methodology: analyzing the publicly available documents from the National Agency for Community Programs in the Field of Education and Vocational Training (ANPCDEFP), monitoring and case studies related to the implementation of Erasmus+ projects, focusing primarily on the first two major stages: the initial mobilization and the follow-up. Our analysis revealed that the formulation and implementation of an Erasmus+ project constitute a strategic necessity for the management of educational institutions, particularly for the professional and personal development of the teaching staff, for internationalizing educational activities, for international cooperation, and for economic growth based on a smart and strict investment in human resources. This is the primary factor influencing the improvement of the quality of the educational system, as the development of teaching skills has both immediate and long-term effects.